PSYCHOLOGICAL CAPITAL DAN PSYCHOLOGICAL EMPOWERMENT TERHADAP PERILAKU KERJA INOVATIF - Viani, Fairdana; Setiawan, Rony; Dian Iva Prestiana, Novita (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2023)
This study aims to examine the significance of the influence of psychological capital and psychological empowerment on innovative work behavior on employees at Arabian Mitra Abadi Company. This study uses a quantitative approach with the whole of 56 employees as respondents, using the study population. This research uses the modified Psychological Capital Questionnaire from Luthans et. al. (2007), the modified Psychological Empowerment scale from Spreitzer (1995), and the modified Innovative Work Behavior Scale from Janssen (2000). The results of the study prove that: (1) Psychological capital has a positive significant effect on innovative work behavior (r = 0,765, n = 56, ρ = 0,000, two tailed); (2) Psychological empowerment has a positive significant effect on innovative work behavior (r = 0,839, n = 56, ρ = 0,000, two tailed) and; (3) Both of psychological capital and psychological empowerment have the influence toward the innovative work behavior of employees (Sig. F = 0,000b, R Square = 0,758).